A randomized fellow-eye controlled trial study of 1% terpinen-4-ol vs 1% tea tree oil eyelid cleanser for the treatment of meibomian gland dysfunction - Saonanon, Preamjit; Witoonchart, Wannit; Charnvanich, Dusadee; Thompho, Somphob; Chaiseeda, Kittichai; Chongpison, Yuda; Satitpitakul, Vannarut (AJO International, 2024)
To compare the pre- and post-treatment differences in non-invasive tear breakup time (NITBUT) between a 1 % terpinen-4-ol (T4O) and a 1 % tea tree oil (TTO) eyelid cleanser A randomized controlled trial Thirty-three participants diagnosed with MGD were enrolled. All patients and the outcome evaluator were masked to the treatment allocation. One eye of each patient was randomly assigned to receive the T4O cleanser, while the fellow eye received the TTO cleanser. Baseline and eight week assessments included the collection of the ocular surface disease index (OSDI) questionnaire, NITBUT (in seconds), lipid layer thickness (in nanometers), ocular surface staining scores, and the presence of Demodex as cylindrical dandruff. The main outcome measurement was the pre- and post-treatment difference in NITBUT. Patient preference, safety, and tolerability were also assessed. There was a statistically significant increase in NITBUT in the T4O group (n = 30; 2.27 ± 1.09; 95 % confidence interval [CI]: 0.12–4.42; p = 0.038), but not in the TTO group (n = 30; 0.04 ± 1.10; 95 % CI: -2.19–2.11; p = 0.972). Both groups showed significant improvement in post-treatment ocular surface staining scores. Fifteen subjects (50 %) preferred TTO due to less cooling sensation experienced during application, nine (30 %) preferred T4O, and six (20 %) had no preference. No major adverse events were observed. Eyelid cleaning with 1 % T4O in MGD for eight weeks was found to increase NITBUT with good tolerability, although it was less preferred compared to TTO.